Development of Oncology Nursing in Nepal: Historical Perspective - Sharma, Sarojini (Nepalese Journal of Cancer, 2020)
Professional nursing in general and oncology nursing in particular underwent significant changes and a distinct paradigm shift in oncology nursing education and practice in the 30 year period of time (1991 to 2020), which promoted the advancement of oncology nursing. This historical review and reflection provides lessons for contemporary clinical cancer nurses, researchers, policy makers and educators to approach the nursing issues, necessity of cooperation/ collaboration and maintaining the passion for increasingly complex nursing specialty.